Perception and Challenges of Preventive Measures of COVID-19 Among Nepalese Frontline Health Professionals: An Unexplored Realism - Krishna Prasad Pathak; Krishna Prasad Pathak; Sandip Das Sanyam; Tara Gaire; Pushpa Babu Basnet; Sanjay Kumar Sah; Buddha Bahadur Basnet; Sujana Pathak; Stan Ingman; Jeremy J. Hoffman (Frontiers Media S.A., 2022)
BackgroundA new coronavirus causes COVID-19, a developing respiratory illness. Unfortunately, there is little information assessing healthcare workers' understanding of technology and preventative strategies during the Nepalese epidemic. Researchers from other subspecialties uncovered some mythical thoughts. As a result, we decided to put it to the test with healthcare personnel on the front lines. The research also looked at the problems experienced by frontline health care personnel (HCP) because of the COVID-19 strategic shift in work policy.MethodsNepalese healthcare workers participated in web-based cross-sectional research. A pre-tested, structured questionnaire utilizing a Google form was used to get self-informed, digitally typed consent, and examine critical perspectives and problems with current technology and COVID-19 prevention efforts.ResultsIn total, 243 participants with mean age of 29.66 ± 7.61 years agreed to participate and were doctors (n = 27), health assistants (n = 2), medical intern doctors (n = 1), paramedical (n = 139), pharmacy (n = 1), and paramedical interns (n = 73) in this study. The calculated mean percentage score of knowledge on instruments and tools was 73.64 (SD ± 10.43) %, and perception on COVID-19 transmission and control was 70.06 (SD ± 18.30) %. At various levels, frontline health workers faced significant challenges, including the adoption of digital health technology.ConclusionFrontline HCPs are anticipated to have updated knowledge from what the study has outlined. It is recommended to follow national guidelines. Policies should be put in place so that every frontline worker can demonstrate high standards in prevention, control, and equipment use that do not create misinformation among HCPs. Throughout, support for digital health materials and disease control methods for HCPs is essential.